NOAA's Space Weather Prediction Center Releases Two New Products. Issue 3 (12th March 2013) - Rutledge, R.; Steenburgh, R.; Viereck, R.; Onsager, T.
Key Points: The NWS SWPC released two new forecast products Forecasts will be in more frequent and more easily understood manner Information is at an appropriate level to meet the sophistication of the users